2020
DOI: 10.1108/mrjiam-06-2020-1065
|View full text |Cite
|
Sign up to set email alerts
|

Stress and myths related to the COVID-19 pandemic’s effects on remote work

Abstract: Purpose The purpose of this paper is to know the implications that COVID-19 has presented in the workplace to develop research strategies related to issues of human and organizational behavior on the business perspective. Design/methodology/approach Quantitative, exploratory based on primary and secondary sources, an online questionnaire was designed and applied with 33 items that was applied in the Mexican work environment, during the period from March 7 to 16, that is, in the same week as WHO made the pand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
1
19

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(106 citation statements)
references
References 27 publications
2
84
1
19
Order By: Relevance
“…In late December 2019, the new and widespread COVID-19 disease started in China and spread rapidly worldwide, and on March 11, 2020, the World Health Organization declared it a pandemic. As of August 25, 2020, there were more than 23.3 million confirmed cases of COVID-19, and more than 800,000 deaths were reported globally 1 , 2 . According to a joint statement by the World Health Organization and the International Chamber of Commerce, COVID-19, with its dual impact on health and the economy, requires immediate action by governments to minimize its transmission.…”
Section: Introductionmentioning
confidence: 99%
“…In late December 2019, the new and widespread COVID-19 disease started in China and spread rapidly worldwide, and on March 11, 2020, the World Health Organization declared it a pandemic. As of August 25, 2020, there were more than 23.3 million confirmed cases of COVID-19, and more than 800,000 deaths were reported globally 1 , 2 . According to a joint statement by the World Health Organization and the International Chamber of Commerce, COVID-19, with its dual impact on health and the economy, requires immediate action by governments to minimize its transmission.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, interpersonal trust determines and improves management processes, influences the nature of interpersonal relationships [75] and job satisfaction [68]. These factors may contribute to employees' resilience to high levels of uncertainty and stress caused by pandemic and remote work [76]. Hence, it seems that it is the interpersonal trust in the organization that can indirectly strengthen the mental wellbeing of employees based on positive job evaluation.…”
Section: The Mediating Role Of Trust In Building Job Satisfactionmentioning
confidence: 99%
“…Research to date has revealed that remote working is gaining attention worldwide, where the number of remote workers expected to increase more (Gómez et al, 2020;Raišienė et al, 2020). Remote work is a working practice that encourages professionals to work beyond the traditional office setting; anywhere they are productive in and that makes work-life balance perfect, and this is based on the idea that there is no need for work to be performed in a particular location (Prasad et al, 2020).…”
Section: Remote Workmentioning
confidence: 99%
“…After reviewing previous studies, the main research topics tackling telework in organizations are the efficiency of virtual teams (Bhat, Pande & Ahuja, 2017), telework features (Raghuram, Hill, Gibbs & Maruping, 2019), virtual leadership (Hoch & Kozlowski, 2014), aspects of mutual trust, effective communication (Rysavy & Michalak, 2020), mental stress and anxiety (Gómez et al, 2020). In addition to the feasibility of remote work in relation to age, gender, and income inequality in Canada (Gallacher & Hossain, 2020).…”
Section: Remote Workmentioning
confidence: 99%